Mechanics of Wood Machining - Csanády, Etele; Magoss, Endre (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Wood is one of the most valuable materials for mankind, and since our earliest days wood materials have been widely used. Today we have modern woodworking machine and tools; however, the raw wood materials available are continuously declining. Therefore we are forced to use this precious material more economically, reducing waste wherever possible. This new textbook on the "Mechanics of Wood Machining" combines the quantitative, mathematical analysis of the mechanisms of wood processing with practical recommendations and solutions. Bringing together materials from many sources, the book contains new theoretical and experimental approaches and offers a clear and systematic overview of the theory of wood cutting, thermal loading in wood-cutting tools, dynamic behaviour of tool and work piece, optimum choice of operational parameters and energy consumption, the wear process of the tools, and the general regularities of wood surface roughness. Diagrams are provided for the quick estimation of various process parameters. This book will be useful for scientists, graduate and postgraduate students, and practising engineers seeking a deeper understanding of physical phenomena associated with real woodworking processes.